2012
DOI: 10.1371/journal.pone.0032718
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Stimulates Glucose Transport in Skeletal Muscle via AMPK Activation: A Contributor to the Beneficial Effects of Coffee on Diabetes

Abstract: Chlorogenic acid (CGA) has been shown to delay intestinal glucose absorption and inhibit gluconeogenesis. Our aim was to investigate the role of CGA in the regulation of glucose transport in skeletal muscle isolated from db/db mice and L6 skeletal muscle cells. Oral glucose tolerance test was performed on db/db mice treated with CGA and soleus muscle was isolated for 2-deoxyglucose transport study. 2DG transport was also examined in L6 myotubes with or without inhibitors such as wortmannin or compound c. AMPK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
141
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(152 citation statements)
references
References 46 publications
8
141
1
2
Order By: Relevance
“…Previous studies have indicated that chlorogenic acid has many potent biological properties [16][17][18]. Additionally, recent reports of chlorogenic acid provide regulatory effects of glucose and lipid concentrations in diabetes and obesity [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that chlorogenic acid has many potent biological properties [16][17][18]. Additionally, recent reports of chlorogenic acid provide regulatory effects of glucose and lipid concentrations in diabetes and obesity [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Antihyperglycemia and antidyslipidemia of GCE might be mediated by CGA activity. CGA affected AMPK signaling pathway [32], upregulated expression of adiponectin [10], upregulated adiponectin receptor gene [30], and increased transcriptional factor of PPAR-α [20] and PPAR-γ [21] which could regulate glucose and lipid metabolism.…”
Section: Lukitasari Et Almentioning
confidence: 99%
“…Phenolic acid conjugates are recognized as antioxidants and have anti-inflammatory properties demonstrated in vitro and in vivo (dos Santos et al, 2006: Prior, 2003Sato et al, 2011). Studies have also reported hypotensive, anti-carcogenic and anti-diabetic effects for these compounds (Ong et al, 2012;Suzuki et al, 2006;Yang et al, 2012) Polyphenol oxidase mediated browning of cut eggplant fruit surfaces due to oxidation of phenolic compounds poses a seeming contradiction for development of eggplant cultivars with improved culinary quality and nutritive value. However, Prohens et al (2007) reported wide variation for browning of cut eggplant fruit surfaces and total phenolics content with only 15% -23% of the total variation for browning attributed to phenolics content.…”
Section: Introductionmentioning
confidence: 99%